Description of Feminism in the Characters ‘Ningsih’ and ‘Aku’ in the Short Story ‘Istri Prajurit’ by Nh. Dini - Riezka Maghfirah; Reza Pahlevi Ginting (Electronic Journal of Education, Social Economics and Technology, 2025)
The short story ‘Istri Prajurit’ by Nh. Dini is one of the Indonesian literary works that reflects the values of feminism through the characters Ningsih and Aku. This research aims to analyze three indicators of feminism, namely discrimination, emancipation, and women's power, using a descriptive qualitative approach that integrates literature study and content analysis based on feminist literary criticism. The analysis shows that the discrimination experienced by Ningsih comes from her family, who reject her marriage to Garjo, a non-bangsawan man, as depicted in Data 1 and 2, which also affects her daughter, Nani, who does not receive financial support for treatment. Women's emancipation is shown through Ningsih's courage to go against social norms by abandoning her family's traditions to marry Garjo (Data 3) and her decision to migrate to Jakarta in search of a better life (Data 4). The character Aku plays a major role in this emancipation by providing moral encouragement to Ningsih and convincing her of her potential. Women's power is seen in Aku, who realizes her worth as a woman, chooses not to continue her relationship with Narto to maintain her life principles (Data 5), and inspires Ningsih to rise from adversity (Data 6). This research reveals the dynamic relationship between discrimination, emancipation, and women's power, showing the struggle against patriarchy and the achievement of independence, making a significant contribution to the study of feminism in Indonesian literature.